Four-dimensional frame structure chlorine-resistant electrode for high-current PEM tank hydrogen evolution

By adopting a four-dimensional frame structure chlorine-resistant electrode in PEM electrolytic seawater technology, combining platinum nanoparticle injection, ion implantation and atomic liquid deposition technologies, a dense protective layer is formed, which solves the problem of easy corrosion of the anode material and significantly improves the stability of the electrode and lifespan improves the application efficiency and commercialization potential of PEM electrolytic seawater technology.

CN119287408APending Publication Date: 2025-01-10BEIJING NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411413332.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing PEM electrolytic seawater technology in the process of electrolyzing seawater and high saline water is easy to corrode, passivate, and has a short life, which limits the application and efficiency of this technology, especially in the problem of wind and power disposal in offshore wind farms. Effective solution.

Method used

The chlorine-resistant electrode is adopted with a four-dimensional frame structure. The dense protective layer is formed by injecting platinum nanoparticles into the cathode, ion implantation and atomic liquid deposition technology at the anode. Combined with graphene modification and gas diffusion layer, the electrode's oxidation resistance and stability are enhanced. sex.

Benefits of technology

It significantly improves the durability and stability of the electrode, extends the service life, reduces costs, and improves the efficiency and commercial application potential of PEM electrolytic seawater technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287408A_ABST
    Figure CN119287408A_ABST
Patent Text Reader

Abstract

The invention relates to a chlorine-resistant electrode with a four-dimensional frame structure for hydrogen evolution of a high-current proton exchange membrane (PEM) tank. The chlorine-resistant electrode is mainly characterized by high brine electrolysis capacity. According to the electrode, a polyarylether high polymer material with a side chain containing a benzimidazole group is adopted as a base membrane, and a platinum ion injected cathode catalyst and a carbon nanotube enhanced gas diffusion layer are combined. According to the anode, an in-situ growth technology is adopted, a flexible three-dimensional organic metal framework composed of a rhenium-praseodymium metal core and a hydrogen bond ligand is constructed, and a dynamic four-dimensional structure is formed under the action of an electric field. Through derivation treatment, graphene surface modification and electrochemical stabilization treatment, the chlorine corrosion resistance and stability of the electrode are remarkably improved. The electrode is novel in structure, can stably and efficiently separate oxygen and assist in hydrogen separation under high current density, has excellent electrochemical performance and long-term operation stability, and is suitable for the new energy field of PEM water electrolyzers and the like.
Need to check novelty before this filing date? Find Prior Art

Description

1. Technical Field

[0001] The present invention relates to the field of electrochemical new energy technology, and specifically to a chlorine-resistant electrode with a four-dimensional framework structure for hydrogen evolution in a high-current PEM cell. The focus is on solving the corrosion and passivation problems of the anode by oxidants mainly composed of chloride ion oxidation products in the process of electrolyzing seawater and other high-salt water in a PEM cell, so as to improve the stability of the anode, extend its service life, and reduce the investment and operation costs of the PEM cell. 2. Background Technology

[0002] In recent years, the green energy sector has made significant progress. By the end of 2023, China's wind power and photovoltaic power generation installed capacity has increased tenfold compared with 10 years ago, and clean energy power generation installed capacity accounts for 58.2% of the total installed capacity. However, the problem of wind power abandonment remains severe. Data show that as of February 2024, the utilization rates of domestic photovoltaic and wind power have both fallen below 95%. In Xinjiang, Gansu and other places, the power restriction rate in areas with insufficient load may even reach 20%-50%. The main reasons for wind power abandonment include insufficient load in the power system, imperfect grid structure, and immature energy storage technology and market mechanisms. When electricity demand is lower than expected, some new energy power generation is forced to abandon due to the inability to access the grid in time. In addition, the relatively lagging construction of the power grid makes it difficult to adapt to the access of large-scale renewable energy, which also exacerbates the problem of wind power abandonment. These data show that despite significant progress in the green energy sector, the problem of wind power abandonment is still serious and needs to be solved by effective measures. By strengthening grid construction, improving market mechanisms, and promoting the development of energy storage technology, it is expected to alleviate the problem of wind power abandonment and further promote the development of green energy.

[0003] The problem of wind and power abandonment is becoming increasingly prominent in the field of green energy, mainly due to power system load fluctuations, grid structure limitations and insufficient energy storage technology. In order to effectively utilize these abandoned wind power and photovoltaic power, a variety of solutions have emerged, among which water electrolysis hydrogen production technology has become an important outlet. The mainstream methods of water electrolysis hydrogen production include alkaline water electrolysis technology (ALK) and proton exchange membrane (PEM) water electrolysis technology. Alkaline water electrolysis technology is mature and low-cost, but it has low efficiency and is difficult to adapt to high current density; while PEM water electrolysis technology has the advantages of low energy consumption, compact equipment, strong adaptability, etc., and can well match the input of renewable energy power. However, PEM water electrolysis technology faces challenges such as short anode material life, easy passivation, and easy deactivation when electrolyzing seawater and high-salt water, which is mainly due to the reaction of a large amount of chloride ions in seawater with the anode material. These problems limit the application of PEM water electrolysis technology in specific environments.

[0004] The development of PEM seawater electrolysis technology is of great significance for solving the problem of wind power abandonment in the construction of offshore wind farms. Due to the intermittent and unstable nature of offshore wind power, a large amount of electricity cannot be consumed in time, resulting in serious wind power abandonment. PEM seawater electrolysis technology can convert this excess electricity into hydrogen to achieve energy storage and utilization. However, the anode materials of PEM seawater electrolysis technology face many challenges, such as chloride ion corrosion, performance degradation and shortened life. Common anode materials for PEM water electrolysis include precious metals such as platinum and iridium, as well as titanium-based oxides (such as iridium oxide, ruthenium oxide, palladium oxide), etc. However, platinum catalysts are easily poisoned when electrolyzing seawater, and iridium is expensive and has limited annual global mining, which limits the widespread application of PEM seawater electrolysis technology. In addition, studies have shown that the repulsion of chloride ions by oxygen anions (sulfate, phosphate, nitrate, etc.) adsorbed on the electrode surface can improve the anode life to a certain extent (about 100 to 1000 hours), but it still cannot meet industrial needs. Therefore, it is particularly important to develop new anode materials with high stability for PEM water electrolysis.

[0005] With the rapid development and industrialization of offshore wind power technology, more and more wind farms are being built at sea, providing broad application prospects for PEM seawater electrolysis technology. However, existing anode materials are difficult to meet the needs of PEM seawater electrolysis technology, which seriously affects the efficiency and stability of the technology. Therefore, it is particularly urgent and necessary to develop new high-stability anode materials for PEM water electrolysis. This is not only related to the commercialization and industrialization process of PEM seawater electrolysis technology, but also to the sustainable development of the entire offshore wind power industry. III. Summary of the invention

[0006] The present invention is made in view of the problems existing in the prior art. Taking iridium oxide anode as an example, during the electrolysis of water, iridium oxide may be damaged and passivated by chlorine and other chlorine-containing oxidants. The main reaction mechanism includes the adsorption and oxidation of chloride ions on the anode surface and the subsequent formation of a passivation film. The main reaction formula includes: the oxidation reaction of chloride ions on the anode surface to produce chlorine:

[0007] 2Cl-2e - →Cl2↑

[0008] The reaction of chlorine gas with iridium oxide results in the chlorination of iridium oxide:

[0009] IrO2+xCl2+yH2O→IrCl x O y (dissolved)+(2-y)OH -

[0010] In addition, chloride ions may also be directly adsorbed on the surface of iridium oxide to form a chlorine-containing passivation film, which hinders the further progress of the electrolytic reaction. The formation of this passivation film is a complex physical and chemical process involving the interaction between chloride ions and the surface of iridium oxide and the subsequent chemical reaction.

[0011] In order to cope with the challenges of corrosion and passivation of iridium oxide anodes during PEM electrolysis of seawater, existing research strategies are mainly aimed at improving the electrode's resistance to chlorine corrosion. For example, by doping or exploring non-precious metals to improve its electrochemical performance and stability, or optimizing electrolysis conditions to reduce chloride ion concentration and chlorine gas generation, and reduce the impact of corrosion. However, these methods may sacrifice electrolysis efficiency or increase costs. Therefore, the present invention innovatively proposes: using platinum nanoparticles to accurately inject base membrane technology at the cathode to improve catalytic performance; the anode first uses ion implantation technology to inject corrosion-resistant metal ions into the anode material to form an inner layer of protection, and then uses atomic liquid deposition technology to form a dense protective layer on the surface. Finally, by precisely controlling the reaction conditions, the directional growth of the four-dimensional framework structure on the anode is achieved, and this four-dimensional framework structure can effectively prevent the penetration effect of chloride ions and their oxidation products (such as chloride oxides), and before it contacts the substrate, it is partially coordinated with the core atoms in the four-dimensional framework structure, but re-dissociated during the Brownian motion induced by the electric field and returned to the electrolyte, thereby avoiding the interference and influence of chloride ions. These innovative measures have laid a solid foundation for the industrial application of PEM electrolysis of seawater technology.

[0012] In order to achieve the above object, the technical solution of the present invention is a four-dimensional framework structure chlorine-resistant electrode for hydrogen evolution in a high current PEM cell, characterized in that the processing of the electrode comprises the following steps:

[0013] Step 1, selecting a side chain polyarylether polymer material as a base film, the material is polyetheretherketone containing a specific sulfonic acid functional group, the degree of polymerization is 7000-9000, the base film thickness is 20 μm, and pretreatment is performed at 120° C. for 2 hours in a nitrogen atmosphere to remove residual solvent and moisture;

[0014] Step 2: Place the pretreated base film in an ion implantation device, implant platinum ions as cathode catalysts at an energy of 30 keV, and control the vacuum degree to be less than 5×10 -6 Pa, the implantation dose is 2×10 12 ions cm -2 , the basement membrane temperature was controlled at 50°C during the injection process;

[0015] Step 3: Flip the base film in the ion implantation device, and implant iridium ions at 20 keV energy on the other side of the base film, and control the vacuum degree to less than 5×10 -6 Pa, the injection dose is 5×10 12 ions cm-2 , the basement membrane temperature was controlled at 50°C during the injection process;

[0016] Step 4, depositing a layer of defective titanium oxide as an intermediate layer on the iridium ion implantation layer obtained in step 3 by atomic liquid deposition technology, the deposition thickness of the defective titanium oxide in each cycle is 0.1 nm, the total thickness is 3 nm, the deposition temperature is 150° C., deionized water and isobutyl titanate are used as precursors, nitrogen is used as a carrier gas, and the gas flow rate is 200 sccm;

[0017] Step 5, on the atomic liquid phase deposition layer obtained in step 4, a flexible three-dimensional organic metal framework consisting of a rhenium metal core, a praseodymium metal sub-core and a hydrogen bond ligand is grown by electrochemical deposition. Specifically, a base film with a defective titanium oxide atomic liquid phase deposition layer is used as a cathode, a platinum electrode is used as an anode, and in an electroplating solution containing 0.1M potassium rhenate, 0.05M praseodymium nitrate, 0.25M 2,4,6-tris(4-carboxyphenyl)-1,3,5-triazine, and 1.0M citric acid, the pH value is adjusted to 3.5, the electroplating solution temperature is 40°C, and electrochemical deposition is performed at a constant potential of -0.6V vs.SCE for 4 hours to slowly grow a four-dimensional framework structure having a rhenium core and a flexible ligand structure;

[0018] Step 6, placing the base film with the four-dimensional framework structure obtained in step 5 in an ethanol solution containing 15% thiourea by mass, reacting at 60° C. for 2 hours, and performing surface derivatization to enhance its stability against chemical corrosion of chlorine and its compounds;

[0019] Step 7, using chemical vapor deposition technology to deposit a layer of graphene on the surface of the derivatized base film obtained in step 6, the deposition temperature is 800° C., the argon flow rate is 100 sccm, the hydrogen flow rate is 50 sccm, and the deposition time is 30 min to improve the stability and conductivity of the electrode;

[0020] Step 8: The graphene-modified substrate obtained in step 8 is used as an anode and a platinum electrode is used as a cathode in an aqueous solution containing 0.5 M sodium sulfate, and the current density is set to 10 mA cm -2 , treated at 80°C for 12 h for electrochemical stabilization to further consolidate the four-dimensional framework structure and improve its durability in the high current PEM cell hydrogen evolution environment;

[0021] Step 9, constructing gas diffusion layers on both sides of the anode and cathode, using a composite material of carbon nanotubes and polytetrafluoroethylene, and forming a gas diffusion layer on the base membrane by a slurry coating method. The mass concentration of polytetrafluoroethylene is 10%. After coating, it is sintered at 350°C for 30 minutes to form a gas diffusion layer with a thickness of 100 to 150μm to ensure good gas transmission and electronic conductivity.

[0022] The present invention is beneficial in that:

[0023] 1) The base film is made of polyetheretherketone containing sulfonic acid functional groups, with precise thickness and specific temperature and humidity treatment, and has mechanical strength and chemical stability, laying the foundation for the electrode.

[0024] 2) Platinum nanoparticles are injected into the cathode base membrane and the air diffusion layer is prepared to ensure air permeability and conductivity, and improve the electrode catalytic and conductive performance. 3) The anode adopts a unique synthesis path of ion implantation, atomic layer liquid deposition and directional growth of four-dimensional framework structure to enhance the electrode stability and conductivity and improve its resistance to chlorine oxidation.

[0025] 4) Finally, the performance and service life of the electrode are improved by finely derivatizing, modifying and stabilizing steps, introducing functional groups, surface modification and heat treatment. IV. Description of the drawings

[0026] In order to more clearly illustrate the specific embodiments of the present invention, the drawings used in the description of the specific embodiments are briefly described below. Figure 1 This is a scanning electron microscope image of the cross-section of the four-dimensional framework structure chlorine-resistant electrode membrane electrode.

[0027] Figure 2 The average order parameter distribution of rhenium atoms in the four-dimensional framework structure with rhenium core and flexible ligand structure at 0ps (a), 5ps (b) and 10ps (c) of molecular dynamics simulation.

[0028] Figure 3 This is a comparison chart of the oxygen evolution overpotential of the four-dimensional framework structure chlorine-resistant electrode membrane electrode and commercial ruthenium oxide, iridium oxide, and ruthenium iridium electrodes. V. Specific implementation methods

[0029] The present invention is described in detail below with reference to the accompanying drawings and embodiments:

[0030] Embodiment 1:

[0031] A chlorine-resistant electrode with a four-dimensional framework structure for hydrogen evolution in a high-current PEM cell, characterized in that the processing of the electrode comprises the following steps: first, a side-chain polyarylether polymer material is selected as a base film, the material is a polyetheretherketone containing a specific sulfonic acid functional group, the degree of polymerization is 7000-9000, the base film thickness is 20 μm, and the base film is pretreated at 120° C. for 2 h in a nitrogen atmosphere to remove residual solvent and moisture; step 2, placing the pretreated base film in an ion implantation device, implanting platinum ions as cathode catalysts with an energy of 30 keV, and controlling the vacuum degree to be less than 5×10 -6 Pa, the implantation dose is 2×10 12 ions cm -2During the implantation process, the base film temperature was controlled at 50°C; the base film was turned over in the ion implantation device, and iridium ions were implanted on the other side of the base film with an energy of 20 keV to form an ion implantation layer with a thickness of 5 nm. The vacuum degree was controlled to be less than 5×10 -6 Pa, the injection dose is 5×10 12 ions cm -2 During the injection process, the temperature of the base film is controlled at 50°C; on the iridium ion implantation layer, a layer of defective titanium oxide is deposited as an intermediate layer by atomic liquid deposition technology. The deposition thickness of the defective titanium oxide in each cycle is 0.1nm, the total thickness is 3nm, the deposition temperature is 150°C, deionized water and isobutyl titanate are used as precursors, nitrogen is used as a carrier gas, and the gas flow rate is 200sccm; on the atomic liquid deposition layer, a flexible three-dimensional organic metal framework composed of a rhenium metal core, a praseodymium metal sub-core and a hydrogen bond ligand is grown by electrochemical deposition. Specifically, the base film with the defective titanium oxide atomic liquid deposition layer is used as the cathode, the platinum electrode is used as the anode, and in a solution containing 0.1M potassium rhenate, 0.05M praseodymium nitrate, and 0.25M 2,4,6-tris(4-carboxyphenyl)-1,3,5-triazine, 1.0M citric acid, pH value was adjusted to 3.5, the plating solution temperature was 40°C, electrochemical deposition was carried out at a constant potential of -0.6Vvs.SCE, the deposition time was 4h, and a four-dimensional framework structure with a rhenium core and a flexible ligand structure (such as the attached Figure 1 The substrate film with the four-dimensional framework structure is placed in an ethanol solution containing 15% thiourea by mass concentration, and reacted at 60°C for 2 hours to perform surface derivatization to enhance its stability against chemical corrosion of chlorine and its compounds; a layer of graphene is deposited on the surface of the derivatized substrate film by chemical vapor deposition technology, the deposition temperature is 800°C, the argon flow rate is 100sccm, the hydrogen flow rate is 50sccm, and the deposition time is 30min to improve the stability and conductivity of the electrode; the substrate film modified with graphene is used as an anode and a platinum electrode is used as a cathode, and is placed in an aqueous solution containing 0.5M sodium sulfate, and the current density is set to 10mA cm -2 , treated at 80°C for 12 hours at constant current for electrochemical stabilization to further consolidate the four-dimensional framework structure and improve its durability in the high current PEM cell hydrogen evolution environment; gas diffusion layers are constructed on both sides of the anode and cathode, and a composite material of carbon nanotubes and polytetrafluoroethylene is used to form a gas diffusion layer on the base membrane by a slurry coating method. The mass concentration of polytetrafluoroethylene is 10%. After coating, it is sintered at 350°C for 30 minutes to form a gas diffusion layer with a thickness of 100 to 150μm, ensuring good gas transport and electronic conductivity.

[0032] Molecular dynamics simulations were performed on the average order parameter distribution of rhenium atoms in a four-dimensional framework structure with a rhenium core and a flexible ligand structure. The average order parameter distribution of rhenium atoms at 0ps (a), 5ps (b) and 10ps (c) under the action of an electric field is shown in the attached figure. Figure 2 It can be seen that under the action of the electric field, the rhenium atoms exhibit periodic oscillations with a vibration period of 10ps, reflecting the "four-dimensional" time characteristics in addition to the three-dimensional structure.

[0033] Embodiment 2:

[0034] The mechanical strength and AC impedance tests were performed on the four-dimensional framework structure chlorine-resistant electrode (referred to as sample) for hydrogen evolution in a high current PEM cell obtained in Example 1:

[0035] Mechanical strength measurement: Cut the sample into strips of 50 mm long and 6 mm wide, and the test length is 20 mm. Take the average of three test results as the final result. Set the stretching rate to 5 mm min -1 The thickness of the membrane was measured. The composite sample had a tensile strength of 16.26 MPa, an elongation at break of 23%-42%, and a Young's modulus range of 0.19-0.20 GPa. Its mechanical strength was superior to that of traditional PEM membranes such as polyethersulfone and polyarylether.

[0036] AC impedance measurement: Prepare the sample into a standard specimen (30×30mm 2 ), tested by four-electrode method, with AC impedance frequency adjusted to 0.1-100kHz, bias amplitude adjusted to 10mV, and measured at 30-80℃, 98%RH humidity (variable temperature and constant humidity). The measurement shows that the proton conductivity of the sample is 0.211-0.166S cm, which is better than the PEM membrane made of PFSA material.

[0037] Embodiment 3:

[0038] A series of electrochemical tests were performed on the samples obtained in Example 1 to verify their electrochemical characteristics and stability. The specific operation method is as follows:

[0039] The electrochemical performance of the samples was evaluated using an electrochemical workstation. The three-electrode system consisted of the sample, a saturated calomel electrode, and a graphite rod. The electrolyte was 0.1 M perchloric acid and the test temperature was 25°C. The oxygen evolution reaction (OER) was carried out in the test range of 0.7-1.7 V vs. SCE. Cyclic voltammetry was used at 50 mV s -1 Then, cyclic voltammetry was performed in the same interval (scan rate: 5.0 mV s -1 ) to test the polarization curve of the working electrode. The test shows that the oxygen evolution overpotential (η 10=236.2mV) is lower than the commercial ruthenium iridium electrode (η 10 =317.2mV), ruthenium oxide (η 10 =316.4mV) and iridium oxide (η 10 =306.9mV) catalyst, with excellent oxygen evolution performance (such as attached Figure 3 shown).

[0040] The Tafel slope is used to analyze the cyclic voltammetry curve in the low overpotential region, and the relationship between the logarithm of the current density and the potential is converted to determine the reaction kinetic rate of the catalyst. The test shows that the Tafel slope of the sample is 58.2mVdec -1 , which is also better than the commercial ruthenium-iridium electrode (90.24mV dec -1 ), ruthenium oxide (60.98mV dec -1 ) and iridium oxide (67.42mV dec -1 ).

[0041] The catalyst stability test was based on a two-electrode test system (Pt sheet as counter electrode and sample as working electrode) using chronopotentiometry in 1.0 M hydrochloric acid medium with a current density of 10 A cm -2 , using the constant current method to test, record the response potential and time curve, and judge the failure time of the catalytic electrode by the increase in overpotential after a long reaction. The test shows that the failure time of the sample (overpotential increases to more than 5 times the original overpotential) is 127h, which is significantly better than the commercial ruthenium iridium electrode (50.2h), ruthenium oxide (36.8h) and iridium oxide (4.2h).

[0042] The specific implementation methods described above are only used to specifically illustrate the spirit of the present invention, and the protection scope of the present invention is not limited thereto. For those skilled in the art, other implementation methods can certainly be easily made by changing, replacing or modifying the technical contents disclosed in this specification, and these other implementation methods should all be covered within the protection scope of the present invention.

Claims

1. A four-dimensional framework structure chlorine-resistant electrode for high current PEM cell hydrogen evolution, characterized in that The electrode processing includes the following steps: Step 1, selecting a side chain polyarylether polymer material as a base film, the material is polyetheretherketone containing a specific sulfonic acid functional group, the degree of polymerization is 7000-9000, the base film thickness is 20 μm, and pretreatment is performed at 120° C. for 2 hours in a nitrogen atmosphere to remove residual solvent and moisture; Step 2: Place the pretreated base film in an ion implantation device and implant platinum ions as cathode catalysts at 30 keV energy. Control the vacuum degree to be less than 5×10 – 6 Pa, the implantation dose is 2×10 12 ions cm – 2 , the basement membrane temperature was controlled at 50°C during the injection process; Step 3: Flip the base film in the ion implantation device and implant iridium ions at 20 keV on the other side, controlling the vacuum degree to less than 5×10 – 6 Pa, the injection dose is 5×10 12 ions cm – 2 , the basement membrane temperature was controlled at 50°C during the injection process; Step 4, depositing a layer of defective titanium oxide as an intermediate layer on the iridium ion implantation layer obtained in step 3 by atomic liquid deposition technology, the deposition thickness of the defective titanium oxide in each cycle is 0.1 nm, the total thickness is 3 nm, the deposition temperature is 150° C., deionized water and isobutyl titanate are used as precursors, nitrogen is used as a carrier gas, and the gas flow rate is 200 sccm; Step 5, on the atomic liquid phase deposition layer obtained in step 4, a flexible three-dimensional organic metal framework consisting of a rhenium metal core, a praseodymium metal sub-core and a hydrogen bond ligand is grown by electrochemical deposition. Specifically, a base film with a defective titanium oxide atomic liquid phase deposition layer is used as a cathode, a platinum electrode is used as an anode, and in an electroplating solution containing 0.1M potassium rhenate, 0.05M praseodymium nitrate, 0.25M 2,4,6-tris(4-carboxyphenyl)-1,3,5-triazine, and 1.0M citric acid, the pH value is adjusted to 3.5, the electroplating solution temperature is 40°C, and electrochemical deposition is performed at a constant potential of -0.6V vs.SCE for 4 hours to slowly grow a four-dimensional framework structure having a rhenium core and a flexible ligand structure; Step 6, placing the base film with the four-dimensional framework structure obtained in step 5 in an ethanol solution containing 15% thiourea by mass, reacting at 60° C. for 2 hours to perform surface derivatization to enhance its stability against chemical corrosion by chlorine and chlorine oxides; Step 7, using chemical vapor deposition technology to deposit a layer of graphene on the surface of the derivatized base film obtained in step 6, the deposition temperature is 800° C., the argon flow rate is 100 sccm, the hydrogen flow rate is 50 sccm, and the deposition time is 30 min to improve the stability and conductivity of the electrode; Step 8: The graphene-modified substrate obtained in step 8 is used as an anode and a platinum electrode is used as a cathode in an aqueous solution containing 0.5 M sodium sulfate, and the current density is set to 10 mA cm – 2 , treated at 80°C for 12 h for electrochemical stabilization to further consolidate the four-dimensional framework structure and improve its durability in the high current PEM cell hydrogen evolution environment; Step 9, constructing gas diffusion layers on both sides of the anode and cathode, using a composite material of carbon nanotubes and polytetrafluoroethylene, and forming a gas diffusion layer on the base membrane by a slurry coating method. The mass concentration of polytetrafluoroethylene is 10%. After coating, it is sintered at 350°C for 30 minutes to form a gas diffusion layer with a thickness of 100μm to 150μm, ensuring good gas transmission and electronic conductivity.